Efektivitas Aplikasi Tangerang LIVE dalam Meningkatkan Kualitas Pelayanan Publik di Kota Tangerang - Irwan Suhender; Tuguatulo Buulolo; Khikmawanto Khikmawanto (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
Efforts to digitize public services are now widely adopted as a strategic move to increase accessibility, speed, and reliability of services. Tangerang LIVE is a technological innovation initiated by the Tangerang City Government to offer integrated access via a digital application. This research investigates the impact of the Tangerang LIVE application in improving public service delivery in Tangerang City from the users’ perspective. The study uses descriptive qualitative methods, involving observations, as well as interviews and document analysis. Informants included personnel from the Tangerang City Department of Communication and Informatics, along with 15 application users. The findings reveal that Tangerang LIVE enjoys a high level of public acceptance, especially in terms of ease of use and usefulness. Nevertheless, challenges remain, particularly in response time and complaint management, which need further attention to address these gaps in service quality. The study suggests improvements to application features and better coordination among internal units to optimize digital public service delivery. Overall, Tangerang LIVE demonstrates strong potential to support bureaucratic reform and deliver more responsive and accountable public services in Tangerang City.